Torsion measurement using Fiber Bragg Grating sensors and a rotary optical coupler - Kim, K.; Lee, J.M.; Hwang, Y. (15th International Congress on Sound and Vibration 2008, ICSV 2008, 2008)
Torsion measurement on a rotating shaft was carried out with FBG (Fiber Bragg Grating) sensors and a rotary optical coupler. Difficulty in measuring torsion in course of shaft rotation remains due to signal transmission between a rotating shaft and a stationary part, thereby conventional methods such as a slip ring, telemetry and FORJ (Fiber Optic Rotary Joints) are dominantly considered as means of transmitting signals. However, the conventional methods maintain inherent problems such as low S/N ratio, high cost, a limited number of channels and inconvenience in installation. In this paper, for the purpose of efficient signal transmission a specially developed rotary optical coupler constituted by two inline C-lenses of 3mm in diameter and small air gap was proposed and compared with FORJ in performance. Two FBG sensors were mounted on the surface of the shaft for measuring strains directly, while one FBG sensor as a reference sensor was installed in the center of the shaft. The reference sensor plays a key role in measuring optical power being used for compensating light intensity loss change in the rotary optical coupler. As a result, the rotary optical coupler combined with the reference sensor shows a superior performance to greatly reduce light intensity loss change, and excellent agreement between measured torsions and applied torsions on the shaft was obtained.